UPAYA MENINGKATKAN PEMBELAJARAN SEPAK TAKRAW MELALUI PERMAINAN BOLA BEREKOR PADA SISWA KELAS V SD NEGERI PETOMPON 01 KOTA SEMARANG (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2015)
The purpose of this study is the Effort to Improve Learning Through Games Bola Sepak Takraw tailed Student In Class V SD Negeri 01 Semarang Petompon. The method used in this study is action research. The data obtained were analyzed with techniques percentage. Acquisition percentage of the first cycle, the average cognitive 39%, average 46% affective aspect, psychomotor aspects of the average 41% with KKM to be achieved is 65%. While the results of the second cycle obtained an average percentage of 69% cognitive, affective average of 72%, an average of 69% with the psychomotor aspects of KKM to be achieved is 65%. Based on the percentage of the acquisition of the first cycle and second cycle can be drawn a conclusion that the use of learning sepak takraw ball tailed in Physical Education and Health Sport can improve learning sepak takraw Elementary School fifth grade students Petompon 01 Semarang.